Respuesta :

Answer:

[tex]m = \frac{1}{2}[/tex]

Step-by-step explanation:

[tex]\frac{y2 - y1}{x2 - x1}[/tex]

[tex]\frac{2-1}{3-1}[/tex]

[tex]2-1 = 1\\ 3-1=2[/tex]

[tex]m = \frac{1}{2}[/tex]

For this case we have that by definition, the slope of a line is given by:

[tex]m = \frac {y_ {2} -y_ {1}} {x_ {2} -x_ {1}}[/tex]

We have two points through which the line passes:

[tex](x_ {1}, y_ {1}) :( 1,1)\\(x_ {2}, y_ {2}) :( 3,2)[/tex]

Substituting:

[tex]m = \frac {2-1} {3-1} = \frac {1} {2}[/tex]

Thus, the slope of the line is [tex]\frac {1} {2}[/tex]

Answer:

Option C

ACCESS MORE